The Importance of Mentorship in Stimulating the Growth and Success of Entrepreneurial Business Entities - Yani, Ahmad; Suherlan; Az Zaakiyyah, Hizbul Khootimah (ADMAN: Journal of Contemporary Administration and Management, 2024)
Entrepreneurs and small businesses play a crucial role in the global economy, particularly as sources of innovation, employment, and local economic growth. However, many entrepreneurial business entities face various challenges, including market uncertainty, intense competition, and a lack of resources and managerial experience. This research aims to examine the role of mentorship in stimulating the growth and success of entrepreneurial business entities. The research method employs a qualitative literature review approach with a focus on exploring relevant literature through Google Scholar. Literature searches were conducted on Google Scholar with a time frame between 2013 and 2023 to ensure inclusivity of recent studies. The study's findings indicate that, in the context of entrepreneurial business, the importance of mentorship proves to be a highly significant element in stimulating growth and success. Mentorship not only serves as a provider of practical advice but also as a source of inspiration, holistic perspectives, and emotional support. Through their experience and wisdom, mentors assist entrepreneurs in overcoming challenges, identifying opportunities, and developing long-term strategies to advance their businesses.